Cultural considerations in forgoing enteral feeding: A comparison between the Hong Kong Chinese, North American, and Malaysian Islamic patients with advanced dementia at the end-of-life - Ngan, Olivia M. Y.; Bergstresser, Sara M.; Emdadul Haque, A. T. M.; Chan, Helen Y. L.; Au, Derrick K. S.; Suhaila Sanip (Wiley, 2024)
Cultural competence, a clinical skill to recognise patients' cultural and religious beliefs, is an integral element in patient-centred medical practice. In the area of death and dying, physicians' understanding of patients' and families' values is essential for the delivery of culturally appropriate care. Dementia is a neurodegenerative condition marked by the decline of cognitive functions. When the condition progresses and deteriorates, patients with advanced dementia often have eating and swallowing problems and are at high risk of developing malnutrition. Enteral tube feeding is a conventional means of providing artificial nutrition and hydration to meet nutritional needs, but its benefits to the frail population are limitedly shown in the clinical evidence. Forgoing tube feeding is ethically challenging when patients are mentally incompetent and in the absence of an advance directive. Unlike some developed countries, like the United States of America, death and dying is a sensitive issue or even a taboo in some cultures in developing countries that forgoing enteral tube feeding is clinically and ethically challenging, such as China and Malaysia. This article in three parts 1) discusses the clinical and ethical issues related to forgoing tube feeding among patients with advanced dementia, 2) describes how Hong Kong Chinese, North American, and Malaysian Islamic cultures respond differently in the decision-making patterns of forgoing tube feeding for patients with advanced dementia, and 3) reiterates the clinical implications of cultural competence in end-of-life care.